High Frequency Spontaneous Deletions within the IcaADBC Operon of Clinical Staphylococcus epidermidis Isolates. - Titik Nuryastuti; Henny C. van der Mei; Henk J. Busscher; Roel Kuijer; Abu Tholib Aman; Bastian P. Krom (Universitas Gadjah Mada, 2012)
Staphylococcus epidermidis has been shown to undergo a phase variation correlating with expression of the icaADBC operon which contributes to biofilm formation. Biofilm formation of Enterococcus faecalis is related to heterogeneity in electrophoretic mobility. Here the relationship between phase variants of clinical isolates of S. epidermidis, icaADBC presence and electrophoretic mobility distributions is investigated. Of 105 S. epidermidis clinical isolates, 5 showed phase variation on Congo Red agar plate. Biofilm forming capability of the blackcolonies and inability of the red colonies were confirmed using a microtiter plate assay and confocal laser scanning microscopy. Upon analysis of electrophoretic mobility distributions, the black colonies displayed heterogeneity at pH 2 which was absent in the red colonies of the same strain. Surprisingly, it was shown that in all red colonies had lost the icaADBC genes. Determination of gene copy number using Real Time PCR targeting icaA showed reduction of gene copy within a culture with phase variation. In conclusion, using three fundamentally different approaches phase variation of the five clinical isolates was observed. Variants appeared through loss of icaA and icaC gens. To our knowledge this is the first report indicating S. epidermidis strains irreversible switching from biofilm + to biofilm – phenotype by deletion of ica genes. Key words: deletion, ica genes, Staphylococcus epidermidis, IcaADBC operon